Prediction of Surface Hardness based on Experimentation of Single Roller Burnishing Operation - Nikhil Shinde, Srinivas Chippalkatti, Abhijeet Deshpande, Mandar Karyakarte, Gajanan Chavhan, Milind Patil (Mathematical Statistician and Engineering Applications, 2023)
In the Present study, effortsare taken to develop an artificial neural network model for predicting surface hardness of single roller burnishing operation. Single roller burnishing operation is designed based on Taguchi orthogonal design matrix. An ANN model was developed based on burnishing process parameters like speed, feed, force and number of passes for prediction using Matlab. It is observed that developed ANN model with accuracy of around 98%